The Role of Technology in Redesigning the Modern Education System - Suhada, Suhada; Khafidoh, Khafidoh; Rosyid, Rosyid; Mudzofir, Mudzofir; Rozin Faiz, Ahmad (JTP - Jurnal Teknologi Pendidikan, 2025)
Technological advancements have played a vital role in redesigning the modern education system to be more adaptive, effective, and inclusive. However, despite rapid development, many educational institutions are still struggling to align with 21st-century competencies due to outdated pedagogical models. This study aims to explore the strategic role of educational technology in transforming modern educational systems, especially within the Indonesian context. Using a qualitative-descriptive method, the research is based on literature analysis of scholarly journals, policy documents, and expert opinions from the last decade. The sample consists of national and international literature relevant to educational technology integration. Findings reveal that the integration of technology in curriculum development, pedagogy, and institutional frameworks has contributed significantly to fostering critical thinking, independent learning, and mastery learning. The study also identifies key educational trends such as personalized learning, system-based approaches, and digital pedagogy. These findings underscore the significance of educational technology as a transformative force in enhancing the relevance and quality of education in the digital era.